Reflections on the nature of populism and the problem of stability. (December 2019) - Rasmussen, David
Beginning with a reference to the concept of the political and the idea of stability, the essay turns to an examination of populism from an historical and a normative point of view. While historically populism can be traced to its Roman origins, from a normative perspective, populism rests on a binary opposition between 'elites' and the 'people'. As such, it undercuts its moral claim to universal representation by taking the part for the whole. In the end, this essay argues that populism cannot provide a moral justification for political stability.